Patient’s psychological experiences during and after recovery from COVID-19 pandemic: a phenomenological study in Pakistan - Farooq Ahmed; Rubina Bhatti; Najma Iqbal Malik; Muhammad Sohaib Haleem; Attia Rehman; Anam Yousaf; Muhammad Saleem; Neelum Kahlid; Rashed Nawaz; Shaoqing Gong (BMC Psychology)
Abstract Background COVID-19 is a transmissible and infectious disease with symptoms similar to pneumonia, ranging from moderate to severe. This study investigated the psychological experiences of patients both during their illness and after their recovery. Methods The study employed purposive sampling and semi-structured interviews to gather insights from 13 COVID-19 survivors (7 women and 6 men). Interpretive Phenomenological Analysis was used to analyze the interview transcripts. Participants ranged in age from 22 to 62 years. Results The analysis identified seven main themes of psychological experiences during the illness, each with several sub-themes. Key themes included denial of the disease, uncertainty about the illness, and psychological distress, which had sub-themes of depression and stress. Other themes included death anxiety, perceived social stigma (with loneliness as a sub-theme), exposure to infection (with restrictions as a sub-theme), and coping strategies (which encompassed active coping and avoidant coping). For experiences post-recovery, two main themes emerged, with eight sub-themes. The first was post-traumatic growth, which included attachment to God, acceptance of death, gratitude (toward God), trust in interpersonal relationships, gratitude toward people, and the significance of life. The second theme was delayed resilience, which involved recovery from insomnia and post-COVID psychological distress. Conclusion The study concluded that surviving COVID-19 involves significant psychological challenges both during the illness and after recovery. These insights are valuable for psychologists and counselors in addressing the emotional and mental health needs of COVID-19 patients.